Fear of cybercrime : lessons for the global e-banking sector - Waller, Lloyd (Ian Randle Publishers KingstonJM, 2015)
Ascertains to what extent fear of cybercrime threatens e-banking and to introduce and sensitise academics, practitioners and policymakers to the importance of including fear of cybercrime as a variable in the challenges to e-banking literature.